The Role of Interleukin 1β (IL-1 β) and Interleukin 6 (IL-6) on Diabetes Mellitus and its Correlation with Cardian Rythm in Wistar Rats (Rattus norvegicus) - Retno Indrawati, - (2023)
Introduction: IL-1 and IL-6 are proinflammatory cytokines produced due to the binding of Advanced Glycation End-products (AGEs). in diabetics, molecularly, diabetes mellitus can be caused by disturbances in the circadian rhythm system. This study aims to determine the role of IL-1β and IL-6 in type 2 diabetes mellitus and their relationship to circadian rhythm. Materials and Methods: This study was conducted on male wistar rats treated with circadian rhythm and increased dietary glucose levels, then measured blood sugar and blood draw from the heart to measure levels of IL-1β and IL-6 using ELISA. Data analysis used One-way ANOVA, repeated measure ANOVA, and Pearson Correlation Test. Results: The dark group showed a significant increase in blood glucose at week 7 (p = 0.039) and 9 (p = 0.002). There was a significant increase in blood glucose at week 9 (p = 0.000) in the light group. There were significant differences between normal, dark, and light groups (p <0.05) at the 9th-week blood glucose level (p = 0.000). In the correlation test, there was a significant relationship with the positive correlation of Interleukin 1 β and blood glucose levels in rats (r = 0.599; p = 0.009), there was a significant relationship between Interleukin 6 and blood glucose levels with positive correlation (p = 0.003; r = 0.652). Conclusion: Circadian rhythm affects the role of Interleukin 1β (IL-1β) and Interleukin 6 (IL-6) in wistar rat with diabetes mellitus.